2016
DOI: 10.1200/jop.2016.013060
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Rivalries and Realigning Goals: Challenges of Clinical and Research Multiteam Systems

Abstract: This article describes the care processes for a 64-year-old man with newly diagnosed advanced non-small-cell lung cancer who was enrolled in a first-line clinical trial of a new immunotherapy regimen. The case highlights the concept of multiteam systems in cancer clinical research and clinical care. Because clinical research represents a highly dynamic entity-with studies frequently opening, closing, and undergoing modifications-concerted efforts of multiple teams are needed to respond to these changes while c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 68 publications
2
37
0
Order By: Relevance
“…This would result in negative multiteam system performance, or failure to achieve a common superordinate goal. This suggests that the direct relationship between a climate of psychological safety and building trust and mutual respect positively impacts multiteam system performance (Gerber et al, 2016). This study therefore proposes that the integration team members' creation of a climate of psychological safety positively impacts trusting relationships between component teams and with the integration team within a multiteam system.…”
Section: Boundary Spanning In Building Trusting Relationships Within mentioning
confidence: 90%
See 3 more Smart Citations
“…This would result in negative multiteam system performance, or failure to achieve a common superordinate goal. This suggests that the direct relationship between a climate of psychological safety and building trust and mutual respect positively impacts multiteam system performance (Gerber et al, 2016). This study therefore proposes that the integration team members' creation of a climate of psychological safety positively impacts trusting relationships between component teams and with the integration team within a multiteam system.…”
Section: Boundary Spanning In Building Trusting Relationships Within mentioning
confidence: 90%
“…Furthermore, a climate of trust, due to psychological safety is an important enabler for successful interdependent relationships (Weaver, 2016). Since an integration team positively impacts multiteam system coordination and interdependence towards achieving a common superordinate goal, it is proposed that the creation of a climate of psychological safety by an integration team aids in building trust, further enhancing multiteam system performance (Gerber et al, 2016). For there to be an element of trust and a cohesive working relationship among component team members, individuals need to feel psychologically safe and that their contributions are valued and taken seriously (Gerber et al, 2016).…”
Section: Boundary Spanning In Building Trusting Relationships Within mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to power struggles, we found that the symptoms of power differentials -that of distrust, disrespect, rivalry and lack of mutual understanding -are themselves barriers to collaboration [61,89,[92][93][94]. Lack of respect and trust prevent collaboration by hampering communication and causing assertiveness to be perceived as threatening [61].…”
Section: Power Differential As a Source Of Power Strugglementioning
confidence: 99%